Antiphagocytic protein 1 increases the susceptibility of Cryptococcus neoformans to amphotericin B and fluconazole. - Muhammad Ghaffar (PLoS ONE, 2019)
Cryptococcus neoformans is a facultative intracellular pathogen responsible for the most common cause of fungal meningioencephalitis, occurring primarily in immunocompromised individuals. Antiphagocytic protein 1 (App1) is a virulence factor produced by C. neoformans that inhibits phagocytosis of the yeast by host macrophages. Treatment of cryptococcosis includes amphotericin B, fluconazole, and flucytosine. Virulence factors have been shown to affect the susceptibility of the pathogen to antifungal drugs. In this study, we aimed to examine the relationship between App1 and antifungal drugs. We found that short-term exposure to amphotericin B downregulates APP1 expression while exposure to fluconazole upregulates APP1. In addition, App1 was found to increase the susceptibility of the yeast to amphotericin B and fluconazole. This study provides evidence of an intricate relationship between App1 and antifungal drugs.